Maternity, Paternity, and Parental Leaves in Europe : Comparison of Family-Related Leave Policies and Key Legal Provisions with Implications for Kosovo - Gotcheva, Boryana (World Bank, Washington, DC, 2020)
Maternity, paternity, and parental leave policies and associated benefits play a significant role in ensuring financial protection at the time of pregnancy, child birth and child raising, and in shaping women’s ability to participate in employment, specifically to get a job and to remain in the labor market after starting a family. This note summarizes the main principles of extending maternity, paternity and parental leave and benefit policies globally and in Europe, highlights new policies and measures, and compares key characteristics such as leave duration and financing in the European countries (EU ad European Free Trade Association (EFTA) member states and Western Balkan countries). This could inform policy making and help assess existing policies and reforms, including in Kosovo.